The impact of using social networking sites on developing social responsibility among Algerian youth as a positive social change (مجلة الواحات للبحوث والدراسات, 2025)
This study aims to highlight the impact of the use of social media sites on the development of social responsibility among Algerian youth. In order to detect this, two tables have been applied, the first to the online addiction scale and the second to the social responsibility scale. The descriptive curriculum has been used on a sample of 90 Algerian youths of both sexes.The study concluded in a sample of university youth that the legal and secure use of social media and other websites makes Algerian youth more involved in their social tasks towards the society in which they live, where they recognize and become familiar with various societal needs. As for religious youth, they are considered Internet addicts. They are unable to perform their social tasks properly because they cannot completely get rid of contact with their devices.Keywords: social networking sites, social responsibility, university youth